The ethics of using Chapter XI as a management strategy - Salem, Mahmoud (Journal of business ethics, 1994)
In the past decade, the use of the Chapter XI has soared to the detriment of many creditors, workers, and consumers. A good number of cases were not based on imminent insolvency, but on firms attempts to avoid litigation claims against them, to terminate labor or other contractual obligations, or to gain new financing., These filings for Chapter XI highlight the use of bank-ruptcy as a strategic option used by management in running a viable organization. This usage is even advised by some academics and management consultants., While such uses may not be illegal, this paper questions the seeming ease with which a firm may use bankruptcy to escape contractual obligations to customers, suppliers, and other stakeholders. It also questions the “ethics” of the academics and management consultants who recommend such usage. Finally, the paper calls for a change in the law in order to minimize the opportunity for the unethical abuse of the bankruptcy law.